Poetic Works and Reflections of Culture and Attitude in Karim Sharaza’s Poetry - Mohamad Maghded Abdollla; Osman Hamad Dashti (QALAAI ZANIST JOURNAL, 2023)
Karim Sharaza is one of the great Kurdish poets and writers. He has served the Kurdish language, literature, art and cultu re for more than 60 years His poems and positions have given great value to his reputation as a Kurdish intellectual. In the field of poetry, he has published three works. Some of his poems have expressed expert views on issues of politics, Kurdish nationalism, struggle and service to literature, art, culture and women. Although we have briefly discussed these issues, but we have tried to show the value of his bright and progressive thought and a drop in the ocean full of gifts of this great Kurdish personality to the readers.